A Marketing Capability Based Export Performance Model for IRAN Software Market - Shahriar Azizi; Vahid Makizadeh; Behtash Jamalieh Bastami (Journal of Information Technology Management)
Increasing non-oil exporting is among the most important concerns for Iran. Software industry is among the knowledge based and profitable ones. Identification of factors affecting export performance of software developers can improve planning that in turn results in increasing software export. In this research a model consisting of seven important variables in software industries including: competitive intensity, marketing planning and executing capability along with three market orientation factors (customer and competition orientation and inter-functional coordination) proposed. Data were gathered by 37-items questionnaire. Questionnaires were completed by senior managers of software companies. Cronbach's ? coefficient was calculated for all latent variables and showed that all coefficients are in acceptable range. For testing the research model we used Smart PLS-Graph 2.0. Results showed competition intensity has positive impact on the competition orientation, marketing execution capability and performance in international market. Findings indicated that competition orientation, marketing execution capability and customer orientation have positive impact on performance in international market. Decomposition effects revealed that the most important factors in affecting international performance are: competition intensity, marketing execution capability, customer orientation and competition orientation, respectively.